Korupsi dalam Perspektif Hukum Islam - Syamsul Anwar (Fakultas Hukum Universitas Islam Indonesia, 2008)
From shariah point of view, a person caught committing corruption shall be penalized. Beside of this, shariah also recognizes a concept so called by ta’zir, it is an authority granted to a person or a body to exercise criminalization policy on cases where Qur’an and Sunnah do not clearly stipulate. Corruption in a case in point. Hence, a government may possesses the freedom to determine the type of penalty which is considered as in conformity with the condition of the society